EKSTRAKSI ANDROGRAFOLID DARI Andrographis paniculata (Burm.f.) Nees MENGGUNAKAN EKSTRAKTOR SOXHLET - Ichwan Ridwan Rais (Universitas Ahmad Dahlan, 2014)
Chemical component extraction from plant herbal influenced by various aspect, such as extraction technique or chemical component character from the plant. Extraction method and solvent polarity exteremly influence chemical component transfer from the cell of plant to solvent solution. Soxhlet is extraction system instrument with frequently same solvent extraction based on liquid-steam circulation process of the solvent. Solvent polarity to extract chemical component of the plant herbal depend on chemical component character it self and ability to penetrate cell membrane. Andrographolide, an active chemical component of Andrographis paniculata has been suggested the most active constituent that responsible to activity of Andrographis paniculata in herbal medication. This chemical constituen has solubility character in solvent with middle polarity that indicates solvent election to extract it. This study shows that chemical component extraction of herbal plant influenced by solvent polarity. Thin Layer Chromatography qualitative analyses indicate that absolute polar and Andrographis paniculata nonpolar solvent could not extract andrographolide, different from middle polarity. Andrographolide extraction with similar solvent and correct method offer extract yield with 16,6% andrographolide.